Suggested Translations for Handling Taboos in Children’s Literature ’Fiction’ in Terms of Zohar Shavit’s Strategies By - سامي حول زينب (Journal of College of Education, 2019)
Abstract A taboo is a cultural, social and religious custom that prohibits people to talk about, do, use or touch a certain thing. Such a phenomenon exists in almost all societies , cultures and ideologies at all times. Facing it while translating, the translator must be perfectly aware of the breakdowns resulting from it especially those related to morals, ideologies and socio- cultural customs in case s/he, the translator, translates these taboos literally because of the differences of the two cultures related to the languages involved. S/he is responsible for adapting or domesticating the texts including these taboos to fit her/his readership . This study attempts to shed light on translated tabooed topics in a number of parallel English into Arabic fictional texts specifically of children’s literature (henceforth ChL), and the solutions via suggested translations set by the researcher , as a mediator , to handle them according to Zohar Shavit’s strategies (1986). The texts are taken from three fictions, i.e. Cinderella, Robinson Crusoe, and Gulliver’s Travels. Each one of the STs has more than one translation. To be objective and judge whether they, the translations, are acceptable or not, the researcher has consulted a three-professor jury specialised in translation to give their opinions about them. Depending on Peter Newmark’s translational method ( 1988) , i.e. communicative translation ,they, the translations, can be a remedial intervention to solve the translator’s two- side dilemma while translating works related to this phenomenon. The first sideis that of being unfaithful to the original in case s/he avoids them; or when accused of indecency , obscenity ,atheism, blasphemy by the society especially by Muslim-Arab one and/orbeing involved in a political opposition when translating them literally. Thus , this study can be helpful for the translators , professional or amateur and to academic people in dealing with them when translating for children.